Peningkatan Kesadaran Masyarakat Terhadap Kekerasan Dalam Rumah Tangga (KDRT) Perspektif Hukum Pidana Di Indonesia - Didik Wahyu S; Teguh Endi Widodo; Nuris Pratama Wisesa; Marwan Marwan; Ruminingsih Ruminingsih; Supriyanto Supriyanto; Sujono Ali Mujahidin (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The problem of domestic violence, hereinafter referred to as domestic violence, is actually a problem that often occurs in married life, but some people, especially in villages, do not consider what they experience as a wrong act in the eyes of the law. Therefore, the public needs to be given an understanding of domestic violence, so that if domestic violence occurs or experiences, the victim can take steps or resolve it legally according to Law Number 23 of 2004 concerning Domestic Violence. The aims of the Community Trial are (1) To provide an understanding of Law Number 23 of 2004 concerning Domestic Violence; (2) To provide an understanding of the forms of legal protection for victims of domestic violence that must be provided by the police; (3) To provide investigators with an understanding of penal mediation in criminal acts of domestic violence. This community service activity is motivated by phenomena that occur in society. This Community Service Activity (PPM) at the Faculty of Law, Sunan Bonang University, Tuban, was attended especially by residents of the Mulyoagung Village Government, numbering approximately 15 people. The activity was carried out at the Mulyoagung Village Hall, Singgahan District, Tuban Regency. carried out by means of socialization and/or providing education through the lecture method. The lecture method was used to explain increasing public awareness of domestic violence (KDRT) from a criminal law perspective in Indonesia on the basis of statutory regulations related to domestic violence and social agendas by distributing donations in the form of money to participants. Overall service activities can be said to be good and successful, seen from the success of the target number of training participants (100%), achievement of training objectives (75%), achievement of planned material targets (80%), and participants' ability to master the material (75%).